Prolonged air leak after IPC insertion: An unusual complication. (2020) - Bhatnagar, Malvika; Slight, Robert; Prasad, Arun Brahmanya; Stanton, Andrew Ewing
Abstract: Indwelling pleural catheters [IPC] have an important role in the management of malignant pleural effusions. We report the development of a significant air leak following IPC insertion with resultant extensive subcutaneous emphysema. The air leak developed, presumably, as a result of visceral pleural disruption, which occurred at the time of vacuum drainage of pleural fluid after IPC placement and not due to lung injury during insertion. The patient required insertion of a large bore intercostal drain connected to low-pressure negative suction. He was eventually discharged home with the aid of an ambulatory system. Although commonly seen in the surgical setting, we believe emergency and respiratory physicians should be aware of the risk of such a complication, and the challenges in its management.